Analysis of Methods for Leak Detection and Monitoring the Main Gas Pipeline Sections - Bohdan Danyltsiv; Olha Khymko (Energy Engineering and Control Systems)
The paper analyzes the existing methods for leak detection and monitoring the main gas pipeline sections. An extended classification of methods is presented based on the additional parameters: operating mode (steady-state, non-steady-state) and type of leak detection (presence detection, location identification, volume determination). Based on the comparative analysis of methods according to criteria of sensitivity, reliability, localization accuracy, response time, and implementation cost, the negative pressure wave method with an extended real-time modeling system was established to be the most effective combination for non-steady-state operation mode and long pipelines. Promising areas for further development of leak detection systems have been identified, including improvement of mathematical models, integration of artificial intelligence methods, enhancement of technical equipment and software.